AN APPLICATION OF FISHERIES CO-MANAGEMENT APPROACH OF IKAN LARANGAN IN WEST SUMATRA, INDONESIA: The Features And Attributes - Indah Susilowati (JOURNAL OF COASTAL DEVELOPMENT, 2001)
“Ikan larangan” is a kind of fisheries management system that applied closing seasons of fishing in a portion of river or canal for certain period. There are three types of ikan larangan’s management: (1) traditional; (2) semi-traditional; and (3) modern. The total sample of 99 household respondents were withdrawn from the three sites of ikan larangan, i.e.: (1) ikan larangan Lubuk landur (traditional, n=19); (2) ikan larangan Kayu Tanam (semi-traditional, n=20); (3) ikan larangan Pasir Lawas (modern, n=60). The study emphasizes more on the modern of ikan larangan system. This is in attempt to find out the possibility of implementing this system to other places in Indonesia as an alternative of resource management system and for food security purpose as well as for enhancing the fisheries sector and the regional developments. Furthermore, the co-management application of ikan larangan could encourage the implementation of decentralization policy in Indonesia since the system may able to help in empowering people and the available resources to generate the local income. Moreover, the salient characteristics of co-management system for ikan larangan could be adopted to prescribe the acceptable resource management for the similar circumstances of the resource in some places in Indonesia.